The Gender Promotion Gap: Evidence from Central Banking - Laura Hospido; Luc Laeven; Ana Lamo (Institute of Labor Economics (IZA), 2019)
We examine gender differences in career progression and promotions in central banking, a stereotypical male-dominated occupation, using confidential anonymized personnel data from the European Central Bank (ECB) during the period 2003-2017. A wage gap emerges between men and women within a few years of hiring, despite broadly similar entry conditions in terms of salary levels and other observables. We also find that women are less likely to be promoted to a higher salary band up until 2010 when the ECB issued a public statement supporting diversity and took several measures to support gender balance. Following this change, the promotion gap disappears. The gender promotion gap prior to this policy change is partly driven by the presence of children. Using 2012-2017 data on promotion applications and decisions, we explore the promotion process in depth, and confirm that during this most recent period women are as likely to be promoted as men. This results from a lower probability of women to apply for promotion, combined with a higher probability of women to be selected conditional on having applied. Following promotion, women perform better in terms of salary progression, suggesting that the higher probability to be selected is based on merit, not positive discrimination.
Keywords: J16; J31; J41; J63; 330; gender gaps; working histories; promotions; central banking